TINGKAT KEBUGARAN JASMANI PADA ANGGOTA MAHASISWA PECINTA ALAM SAGARMATHA STKIP MUHAMMADIYAH KUNINGAN - Al Ghazali, Abdullah Gymnastiar; Rahman, Ramdhani (Journal of Physical Education and Sport Science, 2024)
Orientation: Physical fitness is defined as the ability of a person's body to perform daily work tasks without causing significant fatigue. The higher a person's physical fitness level, the greater their physical ability and work productivity. Research Purpose: This study aims to determine the level of physical fitness in student members of Sagarmatha nature lovers STKIP Muhammadiyah Kuningan by using the 2.4 Km running test (Cooper Test). Method: This research is quantitative research and the research design used is a descriptive survey method. Results and discussioin: The results obtained showed that the average fitness level in members of the Sagarmatha nature lover students of STKIP Muhammadiyah Kuningan did not have a good fitness level with the results of 29.898 ml / kg / min. Conclusion and Implications: Researchers can conclude that the average fitness level of Sagarmatha nature lover student members of STKIP Muhammadiyah Kuningan in 2024 after doing the 2.4 Km running test (Cooper test) is 29.898 ml / kg / minute. The implication of this research is that it is influenced by a lack of exercise and not from sports majors alone.